Perceptions of customer service and intentions to switch in South African retail banking - Stenekamp, Altus Geoffrey (My University, 2014)
There are many studies that focus on customer satisfaction and possible switching in service industries (Keaveney, 1995; Levesque and McDougall, 1996; Mittal and Lassar, 1998). Thus, understanding what leads to customer satisfaction and why they switch from one retail bank to another is vital in order to ensure sustainable profitability. The purpose of this research was to ascertain customers‟ perceptions of the four biggest retail banks in South Africa and to what extent these perceptions can lead to possible switching between banks. This was done by adapting the research of Parasuraman, Zeithaml and Berry (1988) to the South African retail banking context. A conjoint study was undertaken and the results showed that customers have generally positive perceptions of customer service in South African retail banking. They also perceive core service failures to be the most important switching consideration, followed by assurance, reliability and attitude and bank charges. A model depicting a personal threshold where the perceived possible future utility gained from switching to another bank surpasses that of the perceived utility at the current bank was also introduced. By understanding the levels of customer satisfaction, coupled with their needs and switching intentions, retail banks will be able to better understand customer behaviour and possible future switching.
MBA thesis
Keywords: Banks and banking; Retail banking